A review of Legionella transmission risk in built environments: sources, regulations, sampling, and detection - Yao, Xiao Hui; Shen, Fan; Hao, Jing; Huang, Lu; Keng, Bin (Frontiers in Public Health, 2024)
The risk of Legionella transmission in built environments remains a significant concern. Legionella can spread within buildings through aerosol transmission, prompting the exploration of airborne transmission pathways and proposing corresponding prevention and control measures based on building characteristics. To this end, a comprehensive literature review on the transmission risk of Legionella in built environments was performed. Four electronic databases (PubMed, Web of Science, Google Scholar, and CNKI) were searched from inception to March 2024 for publications reporting the risk of Legionella transmission in built environments. Relevant articles and gray literature reports were hand-searched, and 96 studies were finally included. Legionella pollution comes from various sources, mainly originates in a variety of built environments in which human beings remain for extended periods. The sources, outbreaks, national standards, regulations, and monitoring techniques for Legionella in buildings are reviewed, in addition to increases in Legionella transmission risk due to poor maintenance of water systems and long-distance transmission events caused by aerosol characteristics. Air and water sampling using various analytical methods helps identify Legionella in the environment, recognize sources in the built environments, and control outbreaks. By comparing the standard regulations of national organizations globally, the authors further highlight gaps and deficiencies in Legionella surveillance in China. Such advancements offer essential insights and references for understanding and addressing Legionella transmission risk in the built environment, with the potential to contribute to safeguarding public health and building environment safety.